A role for cubesats in responsive space - (:unkn) unknown (My University, 2005)
The concept of Responsive Space calls for rapid deployment of satellites to respond to newly emergent conditions around the World. Cubesats on the other hand have gained a reputation for an easy, quick and low cost way of building satellites based on standardized architecture and components. Furthermore one launch can carry many cubesats into orbit to help form constellations or for short revisit times. The paper reviews the cubesat architecture, its merits and role in responsive space applications.